CULTURE AND EVOLUTION OF BAKPIA PATHOK TASTE AS A GASTRONOMIC TOURIST ATTRACTION IN YOGYAKARTA - Ustradi Osijo, Immanuel; Sudarmiatin; Tri Djatmika RWW, Ery (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
The purpose of this study is to find out the culture, history, and evolution of the taste of